Peluang Peningkatan Pendapatan Petani Padi di Kecamatan Kotabumi Utara dengan Budidaya Padi Kultivar MSP 13B - Sri Puji Lestari; Yuni Elmita Sari; Nyang Vania Ayuningtyas Harini; Uswatun Hasanah; Nabilah Indah Safitri (Jurnal Penelitian Pertanian Terapan, 2026)
Rice is the main food crop commodity because the majority of the Indonesian population consumes rice as a staple food. Using superior seeds can help meet the increasing demand for rice due to population growth. There are local superior seeds that have not been utilized optimally by farmers in Lampung Province, namely MSP rice seeds. Since 2022, farmers in North Lampung Regency, precisely in North Kotabumi District, have been cultivating MSP rice. However, not all farmers cultivate MSP rice. The purpose of this study was to determine the comparison of production between MSP and non-MSP rice, to determine the comparison of income levels of MSP and non-MSP rice farming, and to determine the feasibility of MSP rice farming. The number of respondents was 60 farmers, namely 30 MSP rice farmers and 30 non-MSP rice farmers. Data analysis method uses income calculation using revenue structure and cost structure. Feasibility analysis of farming business uses R/C ratio. MSP rice production is lower compared to non-MSP rice production, which is 3,996.81 kg/ha for MSP rice and 4,113.44 kg/ha for non-MSP rice farming. The profit of MSP rice farming is higher than the profit of non-MSP rice farming both on cash costs and on the basis of calculated costs. The profit on cash costs of MSP rice is IDR 32,652,337.58/hectare and IDR 30,462,768.96/hectare for non-MSP rice. The profit on the basis of calculated costs is IDR 26,913,039.49/hectare for MSP rice farming and IDR 24,486,329.15/hectare for non-MSP rice farming. Based on the R/C ratio analysis, MSP rice farming is feasible to be pursued because the R/C ratio value is >1, which is 3.20 R/C ratio of cash costs and 2.31 R/C ratio of calculated costs. So that MSP rice farming has the potential to increase the income of rice farmers in North Kotabumi District.